The Philippine islands. A political, geographical, ethnographical, social and commercial history of the Philippine archipelago and its political dependencies, embracing the whole period of Spanish rule - Foreman, John; iGLibrary (online resource). (Shanghai Kelly and Walsh, Ltd., 1899)
"Long years of personal acquaintance with some of the active movers in the Revolutionary Party enabled me to estimate their aspirations. My associations with Spain and Spaniards since my boyhood helped me, as an eye-witness of the outbreak of the rebellion, to judge of the counterpart to that movement. My connection with the American Peace Commission in Paris afforded me an opportunity of appreciating the noble efforts of a free people to raise the weight of monastic oppression from millions of their fellow creatures."
The Philippine islands. A political, geographical, ethnographical, social and commercial history of the Philippine archipelago and its political dependencies, embracing the whole period of Spanish rule -- PREFACE TO THE FIRST EDITION -- PREFACE TO THE SECOND EDITION -- CONTENTS -- LIST OF ILLUSTRATIONS -- PROLOGUE -- CHAPTER I. General Description of the Archipelago.-Geographical Features - -- CHAPTER II. Discovery of the Archipelago.-Magellan Straits discovered.-Death of Maghallanes.- The First Voyage round the World.-Expedition to the Moluccas. - Legaspi's Expedition from Mexico.-Manila founded.-Death of Legaspi - -- CHAPTER III. Philippine Dependencies.-The Ladrone, Caroline, and Pelew Islands -- CHAPTER IV. Attempted Conquest by Chinese.-Its Failure.-Fray Alonso Sanchez's Mission to Spain.-Internal Administration in Olden Times.-Mendicant and Augustine Friars.-Supreme Court.-Church and State Contentions.-A Governor-General murdered -- CHAPTER V. Early Relations between the Philippines and Japan.-Catholic Missions.-Martyr Saints -- CHAPTER VI. Conflicts with the Dutch.-Prosecutions of Governor-Generals.- Nunneries.-The Inquisition.-Koxinga, the Chinese Corsair, threatens Invasion.-Valenzuela, the Court Favourite.-Strange Proceedings of a Pope's Legate - -- CHAPTER VII. British Occupation of Manila in 1763.-The War Indemnity.-Simon de Anda's Rebellion.-Manila evacuated under the Treaty of Paris.-Ylocos Province Rebellion.-Struggles for Liberty.-Cavite Conspiracy of 1872 -- CHAPTER VIII. The Chinese.-The Alcayceria.-The Parian.-Expulsion of Chinese decreed.-Chinese as Colonists.-Saint Francis rescues Manila from the Chinese.-Chinese Population -- CHAPTER IX. The Various Tribes and Races.-Negrito Marriage Ceremony.-Expedition against the Igorrotes. - Gaddanes. - Itavis.-Igorrotes.-Igorrote-Chinese.-Tinguianes.-Hindoos.-Albinos -- CHAPTER X. Moslems and Southern Tribes.-Early History of the Sulu Archipelago.-Mussulman Pirates.-Epoch of Terror.-Vicissitudes of Sultan Mahamad Alimudin.-Mussulman Reprisals on the Spaniards.-Colonel Arolas' Victories.-The Marauit Campaign. -Sulu Costumes.-Religious Rites.-Sulu Island.-Subuanos Tribe.-Across Palauan Island -- CHAPTER XI. Domesticated Christian Natives.-Their Supposed Origin.-Character. - Tagalogs. - Visayos. - Education, Schools and Colleges. - Native Talent. - Fine Arts. - Music. - Religious Superstitions.-The Shrines.-Penitents.-Slavery.-Prevalent Diseases.-Marriages.-Mixed Marriages.-Dancing -- CHAPTER XII. The Monastic Orders.-Their Preponderance.-Their Relations with the Natives.-The Spanish Parish Priest.-The Hierarchy. -Church Revenues.-Rivalries of the Friars -- CHAPTER XIII. Government and Local Administration.-The Encomenderos.- The Alcaldes.-Cost of Local Government.-Effects of Favouritism. -Abuses.-Native Provincial Authorities.-Municipal Reforms -- CHAPTER XIV. Philippine Finances.-The Budget.-Army, Navy, and Judicial Statistics.-Brigandage.-Pirates.-Legal Dilatoriness -- CHAPTER XV. Trade of the Islands.-Its Early History.-The Mexican Subsidy.-The Galleons.-Smugglers in Olden Days.-Restrictions on Trade.-The " Companía Guipuzcoanade Caracas."-The "Real Compañía de Filipinas."-Development of Agriculture.-Commercial Crisis.- Free Trade.-Manila opened to the World.-Foreign Capital introduced.-Monetary Notes.-Exchange Fluctuations.-Provincial Ports opened.-Tables of Trade Statistics.-Excise and Customs Statistics.-Smuggling.-Mail Service. - Middlemen. - Manufactures. - Railways. - First Philippine Railway.-Submarine and Land Telegraphs -- CHAPTER XVI. Agriculture.-Value of Arable Land.-Land Measures.-Cane Sugar Statistics.-Sugar Shipments.-Sugar-Planting and Manufacture.-Sugar-Making Estimate.-Cane Sugar v. Beetroot Sugar.-Rice.-Rice Measures.-Rice Cultivation.-Macan and Paga Paddy - -- CHAPTER XVII. Manila Hemp.-Hemp Machinery.-Hemp-Planting Statistics and Estimate.-Hemp Trade.-Hemp Shipments -- CHAPTER XVIII. Coffee.-Coffee Quotations, Shipments and Statistics.-Coffee Culture and Yield.-Tobacco under Government Monopoly.-Tobacco under Free Trade.-Tobacco and Cigar Shipments and Statistics. -The " Compania General de Tabacos de Filipinas " -- CHAPTER XIX. Maize.-Cocoa (Cacao).-Esculent Roots.-Monkey Nuts.-Betel.-Areca Palm.-Nipa Palm.-Cocoanut Palm.-Coprah Shipmentsand Statistics.-Coir.-Cógon.-Cotton. -Dita.-Palma Brava.-Bamboo. - Bojo.-Rattan Cane. - Gum Mastic Shipments.-Edible Birds' Nests.-Balate.-Sapan-wood Shipments.- Saps.-Hard Woods.-Hard Wood Tests, Comparative Strengths and Qualities.-Fruits.-Flowers.-Medicinal Herbs - -- CHAPTER XX. Mineral Products.-Coal.-Gold.-Iron.-Copper.-Sulphur, etc. -- CHAPTER XXI. Domestic Live Stock.-Ponies, Buffaloes, etc.-Reptilia.-Insects, etc.-The Locust Plague -- CHAPTER XXII. Manila under Spanish Rule.-The Port.-The City.-Binondo, the Trading Centre.-Electric Lighting.-Tramways.-Chinese and Native Traders and Workers.-Bridges.-Theatres.-Bull Ring.- Cock-Fighting.-Chinese New Year.-Journalism.-Botanic Garden.-Dwelling-Houses.-Typhoons.-Earthquakes.-Native Costumes -- CHAPTER XXIII. Touring in Luzon Island.-Up the Pasig River.-Laguna de Bay.-Jalajala. - Los Baños. - Santa Cruz. - Pagsanjan. - Botocan Cascade.-Majayjay.-Tayabas and Pagbilao.-San Juan de Bocboc.-Batangas.-Lipa.-Bombón Lake.-Talisay.-Taal.-Balayan.-Maragondon.-Santa Cruz de Malabon.-Silan.-Perez Dasmarinas.-Cavité Viejo.-Cavite -- CHAPTER XXIV. Touring in the South.-Romblon.-The Silanga.-Yloilo.-W. Coast of Negros.-Ginigaran.-Sumag.-Bacolod.-Cadiz Nuevo.-Escalante.-The Danao River.-Calatrava.-Bagumbayan.-Across Negros Island.-Buffalo Riding.-A Horse Fight -- CHAPTER XXV. Travelling Notes.-Itineraries of 22 Journeys about the Islands -- CHAPTER XXVI. The Tagalog Rebellion of 1896-98.-First Period up to the Retirement of the Rebel Leaders to Hongkong.-The alleged Treaty of Biac-na-bato.-Peace proclaimed -- CHAPTER XXVII. The Tagalog Rebellion of 1896-98.-Second Period.-American Intervention.-The Rebel Leaders return under American auspices and resume Warfare. - The Naval Battle of Cavite.- The Effect in Madrid.-The American-Spanish Peace Commission in Paris. - Manila City capitulates to the Americans. - The Revolutionary Government.-Philippine Act of Independence.-First Revolutionary Congress.-The American-Spanish Treaty of Paris -- CHAPTER XXVIII. Concluding Observations -- INDEX.
Includes bibliographical references and index.
Electronic Reproduction.
Keywords: Electronic books; Philippines